The association between alexithymia and internet addiction disorder in a large sample of Chinese undergraduates: the role of sexual assault experiences - Qiu, Fangxinrui; Tang, Wanjie; Hu, Tao; Lu, Xiong; Wu, Siqi; Zhou, Xinyu (Frontiers in Public Health, 2025)
ObjectiveWhile a positive association between alexithymia and Internet Addiction Disorder (IAD) has been established, previous studies are often limited by small sample sizes, lack of representative populations, and insufficient attention to intra-group differences, such as the impact of experiences like sexual assault.MethodAnonymous questionnaires assessing alexithymia and IAD were distributed to approximately 11,000 university students across six institutions in Southwest China, resulting in 7,890 valid responses. In addition to measures of alexithymia and IAD, data were also collected on experiences of sexual assault, psychological distress, and a range of sociodemographic variables.ResultsAlexithymia was directly associated with IAD (r = 0.40), and past experiences of sexual assault were found to exacerbate the negative impact of alexithymia on IAD symptoms, even after controlling for psychological distress and gender. Individuals who had experienced sexual assault reported significantly higher levels of alexithymia, psychological distress, and IAD compared to those who had not.ConclusionTo address the high prevalence of IAD among college students, it is essential to screen for difficulties in emotional identification and expression, and to provide support for improving these skills. Targeted interventions are especially important for vulnerable groups, such as survivors of sexual assault, to help reduce the risk of IAD. Future longitudinal studies are needed to further explore these relationships.